2016
DOI: 10.48031/msunjear.2016.04.07
|View full text |Cite
|
Sign up to set email alerts
|

Pond Based Juvenile Production of Siganids: Growth Performance of 30-Day Post Hatch Siganus guttatus (Bloch, 1787) at Three Stocking Densities

Abstract: Growth performance, survival and profit index of 30-day post hatch Siganus guttatus (0.08 ± 0.09 g and 1.60 ± 0.15 cm) of the same age group was evaluated for 60 days in hapa net cages (1m wide x 1m long x 1m deep) in pond based conditions. Three stocking densities were replicated three times and laid out using Completely Randomized Design (CRD). The three treatments were: 1(T1)-250 fish m -3 ; 2 (T2)-500 fish m -3 and 3 (T3)-1000 fish m -3 . Growth performances (final weight, weight gain and specific growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…The results of this study are in agreement with the findings of Andam et al (2016) who reported a 23.90 mm increase in the S. guttatus during the fingerling period.…”
Section: Growth Rate At Different Protein Levelssupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study are in agreement with the findings of Andam et al (2016) who reported a 23.90 mm increase in the S. guttatus during the fingerling period.…”
Section: Growth Rate At Different Protein Levelssupporting
confidence: 93%
“…Another study by Hieu et al (2018) found these proteins contents levels in diets also showed the highest value of growth rate. The survival rate in this study was higher than that reported by Andam et al (2016) when using a diet with a protein level of 30 -40%, which was mentioned as the best growth of the species at 40% CP in the diet. However, the species in the brackish water of Tam Giang lagoon had different characteristics, there was no successful result by artificial reproduction yet and there were still more biological mysteries.…”
Section: Daily Gain and Lengthscontrasting
confidence: 80%
See 1 more Smart Citation
“…In addition to increase in weight, increases in length is an important factor to evaluate during the development in the ngerling stage. This study showed that the average growth belongs the length of sh from 30 to 60 days old (Table 3), detail growth of sh at 35% CP reached 36.92 mm sh -1 which was lower than that those in the 45% CP feed group, which had a length of 38.89 mm sh -1 (p < 0.05) but was not distinct from the remaining 40% CP fed group (37.97 mm sh -1 ); meanwhile, the increase in length of formulas 1, 2 and 3 reached 18.66, 19.73 and 20.62 mm sh -1 , respectively (p > 0.05), and the length of S. guttatus during the ngerling period increased to 23.90 mm (Andam, 2016). Daily length growth (DLG) of the 3 experimental treatments were as follows:…”
Section: Growth Rate At Different Protein Levelsmentioning
confidence: 77%